Promoteurs de réseaux et pratiques sanitaires : Médecins français à l’œuvre lors de l’éclosion de fièvre jaune de 1857 à Montevideo - Nancy González Salazar (Les Cahiers ALHIM)
Based on a case study, that of the first yellow fever outbreak in Montevideo, this article highlights the role played by a group of French doctors and pharmacists based in Uruguay in the management of the plague and the impact of their intervention during this epidemic crisis on the whole of society. By contrast, it reveals the weakness of the regulatory institution of local medicine and its complex relationships with other societal actors (the population, members of the church, etc.), as well as the lack of cohesion among members of the medical sphere and the degree of ignorance that then existed about the yellow fever, all of which have slowed down the implementation of measures by the medical institution.